The Concept of Fiscal Policy: an Islamic Economic Perspective - Renny Oktafia; Ririt Iriani; Reinanda Aprilia Putri Rochimin (JOURNAL OF SHARIA ECONOMICS, 2023)
This article explores the concept of fiscal policy from an Islamic economic perspective. Fiscal policy is a vital tool used by governments worldwide to manage the economy and achieve desired macroeconomic objectives. In the context of Islamic economics, fiscal policy is shaped by principles derived from Islamic teachings and ethical guidelines. The paper begins by providing a comprehensive overview of the core principles of Islamic economics, highlighting its emphasis on justice, equity, and the prohibition of interest (riba). In an Islamic economic perspective, fiscal policy aims to promote social welfare, reduce income inequality, and ensure the fair distribution of wealth. The paper examines how Islamic fiscal policy instruments, such as zakat (obligatory alms), waqf (endowment), and sadaqah (voluntary charity), are employed to achieve these goals and contribute to sustainable economic growth. In conclusion, this paper offers a comprehensive exploration of fiscal policy from an Islamic economic perspective, shedding light on the fundamental principles that guide fiscal decision-making within an ethical framework. It emphasizes the importance of incorporating Islamic economic values in crafting fiscal policies that promote social justice, equitable distribution of resources, and sustainable economic development. The findings of this study have implications for policymakers, economists, and practitioners interested in incorporating ethical and value-based dimensions into the design and implementation of fiscal policies in both Muslim-majority countries and the global economic community.